(untitled) (Research, Society and Development, 2020)
The aim of this article is to present a research instrument (Sport Management in States and Municipalities), aimed at broadly surveying municipal public sport policies in Brazil, as well as the theoretical and methodological foundations that support it. It is important to note that this instrument aims to be applicable / useful / viable for all (or very close to) the municipalities in Brazil.